Pengaruh Penerapan Metode Role Playing Berbantuan Media Cerita Berantai terhadap Hasil Belajar Siswa Kelas V - Maran, Maria Vigilina Lena; Bunga, Maria Herliyani Dua; Lawotan, Yohanes Ehe (Universitas Muhammadiyah Magelang, 2025)
This study aims to determine the effect of applying the role playing method assisted by chain story media on the learning outcomes of fifth-grade students at SDK Maria Ferrari. The study used an experimental method with a One Group Pretest–Posttest design. There were 29 students who were all included in the sample. The research instruments were formative and summative tests, which were used as pretest and posttest. The data were analyzed using normality tests and paired t-tests. The results of the analysis showed that the average pretest score of 81.6 increased to 92.8 on the posttest. The results of the paired t-test showed a significance value of p < 0.001, which means that there was a significant difference between the learning outcomes before and after the treatment. Thus, it can be concluded that the application of the role-playing method assisted by chain story media had a significant effect on improving student learning outcomes. This method was also proven to be able to increase student activity, motivation, and involvement in the learning process.